Prevalence of hepatitis E virus in China from 1997 to 2022: a systematic review and meta-analysis - Cao, Kexin; Wu, Xiaoyue; Yang, Mengya; Chen, Can; Zhang, Xiaobao; Jiang, Daixi; Du, Yuxia; Chen, Mengsha; You, Yue; Zhou, Wenkai; Qi, Jiaxing; Chen, Dingmo; et al. (Frontiers in Public Health, 2023)
Several studies have reported on hepatitis E virus (HEV) prevalence in various regions of China, but the results vary widely. Herein, we conducted a systematic review and meta-analysis to assess the seroprevalence, RNA-positive rate, genotype distribution of HEV in China, and its risk factors. We included 208 related studies involving 1,785,569 participants published between 1997 and 2022. Random-effects models were used to pool prevalence, and subgroup analyses were conducted by population, gender, age, study period, regions, and rural-urban distribution. The meta regression models and pooled odds ratios (OR) were performed to identify risk factors for HEV infections. The pooled anti-HEV IgG, IgM, and Ag seroprevalence, and RNA detection rates in China from 1997–2022 were 23.17% (95% confidence interval (CI): 20.23–26.25), 0.73% (95%CI: 0.55–0.93), 0.12% (95%CI: 0.01–0.32), and 6.55% (95%CI: 3.46–12.05), respectively. The anti-HEV IgG seropositivity was higher in the occupational population (48.41%; 95%CI: 40.02–56.85) and older adult aged 50–59 years (40.87%; 95%CI: 31.95–50.11). The dominant genotype (GT) of hepatitis E in China was GT4. Notably, drinking non-tap water (OR = 1.82; 95%CI: 1.50–2.20), consumption of raw or undercooked meat (OR = 1.47; 95%CI: 1.17–1.84), and ethnic minorities (OR = 1.50; 95%CI: 1.29–1.73) were risk factors of anti-HEV IgG seroprevalence. Overall, the prevalence of hepatitis E was relatively high in China, especially among older adults, ethnic minorities, and humans with occupational exposure to pigs. Thus, there is a need for preventive measures, including HEV infection screening and surveillance, health education, and hepatitis E vaccine intervention in high-risk areas and populations.